LANGKAH BERSAMA : PERAN MAHASISWA TEOLOGI DALAM MEWUJUDKAN KEESAAN GEREJA - Panjaitan, Susilawati; Situmorang, Meditatio (JURNAL KADESI, 2024)
This article is titled "Joint Steps: The Role of Theology Students in Realizing Church Unity." Church unity is a fundamental concept in the Christian faith that emphasizes the importance of unity among various denominations. In an increasingly complex global context, divisions and the emergence of new sects threaten dialogue and cooperation between churches. Therefore, theology students have a crucial role in fighting for unity through the Ecumenical movement. Using a qualitative research method that relies on library data collection, this article investigates how theology students can contribute to organizing seminars, interdenominational worship, and social service projects. Their active participation in the Ecumenical movement is expected to overcome skepticism and strengthen cooperation between churches. Through these steps, theology students not only understand the unity of the church but can also become agents of transformation that bring to life the values ??of unity. Thus, the church can become a stronger witness in the world, reflecting the universal love of Christ.